Activities to Enhance Pupils’ Reading Skills (Maharatul Qiraah) in Arabic Language Learning - Amalia Muhazlin Sitorus; Akmal Walad Ahkas (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
Students at madrasas still face difficulties reading Arabic texts, so efforts are required to help pupils develop their abilities. The purpose of this study was to describe initiatives made to help students' reading abilities as they studied Arabic. This study's context can be found at MAN Sibolga. This study combined an analytical descriptive study method with a qualitative approach. Participant observation techniques, in-depth interviews, and documentation studies are used for data collecting. Data analysis presents facts to reach a conclusion while utilizing data reduction strategies. Observation persistence and data triangulation procedures will be used to assess the validity of the research data. The findings of this study showed that the madrasah's efforts to improve students' reading abilities in learning Arabic included: (1) giving students ten vocabulary lists to memorize at each session; (2) teaching students to read aloud in pairs; and (3) testing students' direct reading every half-semester. By making these efforts, teachers can gradually aid students in developing their reading comprehension of Arabic texts.